Diretrizes para o monitoramento da eficácia da manutenção de itens importantes à segurança para o submarino de propulsão nuclear brasileiro - Filho, Rubens Alberto de Oliveira (2018)
This work presents a set of guidelines for planning maintenance effectiveness monitoring in the design, development and production phases of a nuclear submarine and its support system. These guidelines aim to produce information necessary for the implementation of a program to monitor the effectiveness of the maintenance of a nuclear submarine and its support system during the phases of operation and support of its life cycle. To support the suggested guidelines, the main characteristics of the life cycle of a system were presented, with the definition of phases, main activities and processes. As a suggestion for the application of the proposed guidelines, the methodology of integrated logistic support was presented, favoring a systemic approach to the planning of the monitoring of the effectiveness of the maintenance of the nuclear submarine set and its support system. The main characteristics of a nuclear submarine that influence the maintenance effectiveness monitoring activities were considered in the proposed guidelines.